1996
DOI: 10.1111/j.1651-2227.1996.tb14155.x
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of Salmonella gastrointestinal infection in Italian children

Abstract: A case‐control study of 85 cases with non‐typhoid Salmonella gastroenteritis, 85 outpatient controls and 79 inpatient controls was conducted among children in Monfalcone, north‐east Italy, between June 1989 and June 1994. Logistic regression was used to evaluate the effect of demographic and socioeconomic characteristics, duration of breastfeeding, history of intestinal illnesses and household diarrhoea, and the recent use of antimicrobials. Breastfeeding was the single most important factor associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…A 1996 case-control study conducted in Italy by Borgnolo, et al reported that children with non-typhoidal salmonellosis were more likely to have unemployed fathers and fathers who worked in non-blue collar jobs than controls (36). A 2010 case-control study conducted in the US by Yonus, et al found no association between SES and salmonellosis (37).…”
Section: Resultsmentioning
confidence: 99%
“…A 1996 case-control study conducted in Italy by Borgnolo, et al reported that children with non-typhoidal salmonellosis were more likely to have unemployed fathers and fathers who worked in non-blue collar jobs than controls (36). A 2010 case-control study conducted in the US by Yonus, et al found no association between SES and salmonellosis (37).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that include infants have suggested that breast-feeding is associated with a decreased risk of salmonellosis [12][13][14][15]. However, studies have failed to show associations between infant salmonellosis and risk factors described for adults and older children [13,[16][17][18].…”
Section: -4838/2004/3808s3-0020mentioning
confidence: 99%
“…Consistent with FoodNet data, it was found that percent African American and Hispanic population were positively associated with incidence of salmonellosis as was percent urban and number of food handlers in the population. A study of Italian children also previously associated “low social class” with incidence of Salmonella infection [3]. …”
Section: Incidence Rates Of Foodborne Illness Among Low Socioeconomentioning
confidence: 99%
“…Incidence rates of foodborne illness have not traditionally been tracked by race, ethnicity or income. A limited number of studies have found that low income populations are more likely to experience greater rates of gastrointestinal illness [2,3,4,5,6]. There is also growing evidence that individuals of minority racial and ethnic groups suffer from greater rates of some foodborne illnesses [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%